1990
DOI: 10.1163/156853990x00185
|View full text |Cite
|
Sign up to set email alerts
|

Routine Formation and Flexibility in Social and Non-Social Behaviour of Aggressive and Non-Aggressive Male Mice

Abstract: To investigate the relationship between aggression and routine-like behaviour the response of male mice of bidirectionally selected lines for attack latency to a change in the social and non-social environment has been measured. In a non-social situation the extent of routine-like behaviour was measured in a Y-maze in which only one of the two arms gave access to the food compartments. The number of errors made in response to reversal of the arm that was blocked was taken as indicator for the degree of routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 180 publications
(48 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…The behavioral and physiological characteristics of birds of the HFP and LFP line show considerable analogy to the characteristics of respectively the proactive (active) and reactive (passive) coping strategy, known to exist in other species like rodents [2] and pigs [9,39]. In mice, it has been shown that proactive copers are more intrinsically driven.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The behavioral and physiological characteristics of birds of the HFP and LFP line show considerable analogy to the characteristics of respectively the proactive (active) and reactive (passive) coping strategy, known to exist in other species like rodents [2] and pigs [9,39]. In mice, it has been shown that proactive copers are more intrinsically driven.…”
Section: Introductionmentioning
confidence: 74%
“…They easily develop routines, a rather rigid form of behavior. In contrast, reactive copers are more flexible and react more to environmental stimuli [2,24]. There is a growing body of evidence that adopting a proactive coping strategy makes an individual more vulnerable to develop behavioral abnormalities than a reactive individual (see, for a review, Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAL mice also attack anesthetized opponents in neutral environments [Natarajan et al, 2009]. The SAL mice additionally attack their female cage-mates in particular after cage cleaning or after repeated inter-male interactions in the resident-intruder paradigm [Benus et al, 1990]. This indiscriminate behavior was clearly different from the two other high-aggression mouse strains in that the latter displayed a rich agonistic repertoire of behaviors and aimed at neither the anaesthetized male opponents nor their female cage-mates [Caramaschi et al, 2008;Natarajan et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of SAL mice routinely attacked unfamiliar male opponents upon repeated interactions [Benus et al, 1990;Caramaschi et al, 2008]. These intense agonistic interactions are relatively insensitive not only to the docile opponent but also to human interferences after the tests [personal observations].…”
Section: Introductionmentioning
confidence: 99%